Analisis Perancangan Desain Formulir Elektronik Ringkasan Masuk Keluar di RSAU dr. Siswanto - Fadilla Rizky Nurhidayat; Wahyu Wijaya Widiyanto; Sri Wulandari (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Medical record form design is a person's creative activity on a medical record form with the function and purpose of conveying information to everyone whose format has been arranged as needed. At the place of this research, namely RSAU dr. Siswanto still uses a mixed hybrid system of electronic medical records and manual medical records. The purpose of this study was to help transfer from manual medical records to electronic medical records. This research method uses the Waterfall model system development. The result of this research is an information system design in the form of a web application with XAMPP database storage.